Historical Population Database of Transylvania. Sources, Particularities, Challenges, and Early Findings - Luminița Dumănescu; Mihaela Hărăguș; Angela Lumezeanu; Elena Crinela Holom; Nicoleta Hegedűs; Daniela Mârza; Diana Covaci; Ioan Bolovan (Historical Life Course Studies)
The Historical Population Database of Transylvania (HPDT) is a research tool for population studies developed since 2014 at the Centre for Population Studies in Cluj-Napoca, financed by an SEE-Norway Grant. HPDT employs a source-oriented approach for recording data from the parish registers kept by the Transylvanian churches, focusing primarily on the main vital events such as births, marriages, and deaths. The data entry process was followed by the standardization of various information, such as names, occupations, locations and causes of death, thus allowing the initiation of a linkage process. The database has already been employed in a wide-ranging series of analyses conducted on datasets extracted from HPDT, which include infant and adult mortality, nuptiality and age at first marriage, social mobility, and the medicalization of childbirth. The wealth of information it includes will enable many more scientific investigations.